Hubungan Perilaku Pencegahan Komplikasi dengan Kualitas Hidup dan Stabilitas Tekanan Darah pada Pasien Hipertensi di Puskesmas Kecamatan Pondok Gede, Bekasi Tahun 2013 - Evi Vestabilivy; Siti Rukayah (Jurnal Persada Husada Indonesia, 2014)
Based on monthly reports obtain from Pondok Gede Health Center, Bekasi East Jakarta onnumber of primary hypertension patients in 2012 with total of 1028 people, the monthlyaverageof 86 visitors were treated of hypertension. Hypertensive patients at Pondok Gede Health CenterBekasi are the seconf highest figure after the ARD. This condition can cause a variety ofcomplications which will impact the quality of life of hypertensive patients. This study designed toinvestigate the relationship between behavioral prevention of hypertension complications withthe quality of life in patients with hypertension and also to analyze the relationship betweenquality of life and blood pressure stability in hypertensive patients. The method used in this studywas a descriptive cross sectional associative with a total sample of 46 patients with hypertensionwho visited Pondok Gede Sub-district health centers in June-July 2013. Questionnaires were usedfor data collection on behavioral prevention of complications and quality of life WHOQOL – BREFwith data analysis process using the statistical test which is chi-square test. The results showed noassociation between physical activity/sport activity with the quality of life of patients withhypertension. There are relationship differences between salt restriction in woman and malehypertensive patient’s quality of life but there is no relationship with the blood pressure stability inhypertensive patients. There are differences in the relationship between behavioral prevention ofcomplications with the quality of life of patients with hypertension but there is no relationshipbetween quality of life with the stability of blood pressure in hypertensive patients. Quit smoking,limiting alcohol intake and stress management are some of the behaviour needs to be consider forfuture research which has no relationship with the quality of life in this study, thiscan be exploredfurther by using in-depth interviews or Focus Group Discussion. Predictor variables can affect thestability of blood pressure such as medication adherence and routine blood pressure control havenot measured in this study which can be further investigated.